Phosducin-Like Protein 1 is Essential for G-Protein Assembly and Signaling in Retinal Rod Photoreceptors - Lai, Chun Wan J. (Society for Neuroscience, 2013)
G-protein β subunits perform essential neuronal functions as part of G-protein βγ and Gβ(5)-regulators of G-protein signaling (RGS) complexes. Both Gβγ and Gβ(5)-RGS are obligate dimers that are thought to require the assistance of the cytosolic chaperonin CCT and a cochaperone, phosducin-like protein 1 (PhLP1) for dimer formation. To test this hypothesis in vivo, we deleted the Phlp1 gene in mouse (Mus musculus) retinal rod photoreceptor cells and measured the effects on G-protein biogenesis and visual signal transduction. In the PhLP1-depleted rods, Gβγ dimer formation was decreased 50-fold, resulting in a >10-fold decrease in light sensitivity. Moreover, a 20-fold reduction in Gβ(5) and RGS9–1 expression was also observed, causing a 15-fold delay in the shutoff of light responses. These findings conclusively demonstrate in vivo that PhLP1 is required for the folding and assembly of both Gβγ and Gβ(5)-RGS9.